2016 IEEE 23rd International Conference on Software Analysis, Evolution, and Reengineering (SANER) 2016
DOI: 10.1109/saner.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Do Code Smells Impact the Effort of Different Maintenance Programming Activities?

Abstract: Abstract-Empirical studies have shown so far that code smells have relatively low impact over maintenance effort at file level. We surmise that previous studies have found low effects of code smells because the effort considered is a "sheer-effort" that does not distinguish between the kinds of developers' activities. In our study, we investigate the effects of code smells at the activity level. Examples of activities are: reading, editing, searching, and navigating, which are performed independently over diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…An exploratory survey on code smells has been performed by Yamashita et al [9]: their results showed that a large proportion of developers did not know about code smells. Soh et al [10] conducted a study where professionals were hired to perform maintenance tasks on functionally equivalent Java projects in order to assess whether code smells a↵ect maintenance activities. Another empirical study on understanding maintenance problems related to code smells, has been done by Yamashita [11].…”
Section: Related Workmentioning
confidence: 99%
“…An exploratory survey on code smells has been performed by Yamashita et al [9]: their results showed that a large proportion of developers did not know about code smells. Soh et al [10] conducted a study where professionals were hired to perform maintenance tasks on functionally equivalent Java projects in order to assess whether code smells a↵ect maintenance activities. Another empirical study on understanding maintenance problems related to code smells, has been done by Yamashita [11].…”
Section: Related Workmentioning
confidence: 99%
“…Maintainability [11], [100], [82], [137], [136], [138], [119] Effort/Cost [117], [120], [105], [68] Reliability [51], [47], [139], [12], [81], [56] Change proneness [88], [56], [139], [ A high number of smells (and hence high technical debt) negatively impact the morale and motivation of the development team and may lead to high attrition [125,123].…”
Section: Software Productmentioning
confidence: 99%
“…[4]), all the way to very low-level activities, such as microtasks [16], activities for incremental change [17] or interactions with code elements (classes, methods and even lines) and commands used [7], [8], [18]- [22]. Soh et al [23] examine developers' efforts on such activities. Based on an extensive literature survey of empirical studies in the area, we came up with a coding of developer activities that is illustrated in Figure 1.…”
Section: A Studies On Developers' Activities During Change Tasksmentioning
confidence: 99%
“…Editing code (adding, altering, removing) [2], [3], [7], [8], [12]- [15], [23] Editing test code [16], [19], [21] Editing functionality [16], [19] Write function description [16] Write call [16] Planning changes [3], [12], [13], [16] Understanding code [7], [13], [14], [23] Searching/locating/finding code and/or initial focus points [4], [14], [16], [17], [23] Searching for a string [2] Locating var definition/use [12] Navigating code dependencies and relating code [4], [7], [8], [23] Navigating static/indirect dependencies [2] Observing program execution [8], [12]- [15] Forming/investigating hypotheses, developing/answering questions [12], [13] Understanding a specific code element (Understanding subgraph [4])…”
Section: B Field Studymentioning
confidence: 99%